Role of rosuvastatin and pitavastatin in alleviating diabetic cardiomyopathy in rats: Targeting of RISK, NF-κB/ NLRP3 inflammasome and TLR4/ NF-κB signaling cascades. - Dalia O Saleh; Nesma M E Abo El Nasr; Marawan A Elbaset; Marwa E Shabana; Tuba Esatbeyoglu; Sherif M Afifi; Ingy M Hashad (PLoS ONE, 2025)
Diabetic cardiomyopathy (DCM) is a serious outcome of type II diabetes mellitus (T2DM) and a key contributor to high morbidity and death in diabetic individuals. The current research is intended to elucidate and compare the therapeutic benefits of rosuvastatin (RVS) and pitavastatin (PTS) in mitigating DMC-induced in rats and exploring the possible underlying molecular signaling pathways. DCM was prompted by feeding rats a high-fat/fructose (F/Fr) diet for eight weeks with a sub-diabetogenic dose of streptozotocin (35 mg/kg; i.p) injection at week seven. All rats were allocated into four groups: a normal control group, a DCM-induced positive control group, the RVS group of DCM-induced rats that were treated once daily with 10 mg/kg of RVS, and the PTS group of DCM rats that were treated with 0.8 mg/kg of PTS. Rats were given the treatments orally for four consecutive weeks. The outcome of the existing work discovered that RVS and PTS significantly improved T2DM-associated DCM, as evidenced by the amelioration of glucose, lipids, cardiac markers, ECG parameters, and redox status. Considering the relationship between oxidative stress and inflammation, this attenuation was evidenced by the downregulation of redox, inflammatory, and cellular fibrotic cascades, namely RISK, NF-κB/NLRP3 inflammasome, and TLR4/NF-κB signaling pathways. Additionally, the histopathological examinations confirmed these structural alterations in the myocardium. Besides, RVS and PTS diminished the expression of caspase-1 assessed by immunochemical staining. In summary, the present study demonstrated that RVS and PTS mitigated the metabolic abnormalities associated with T2DM-induced DCM.